A Review on IT Strategy Themes of Accounting Firms - Ronald Aloysius Romein; Glenny Chudra (Green Publisher Indonesia, 2024)
Currently, the growth of information technology is rapidly evolving alongside the journey of a business entity, as seen in public accounting firms facing demands to effectively utilize technology to enhance efficiency, productivity, and service quality. Identifying several challenges that may arise in the implementation of information technology strategies, including information security issues, investment costs, complex system integration, and organizational cultural challenges, public ac- counting firms are advised to pay attention to specific aspects in designing and implementing information technology strategies, such as selecting appropriate technology, employee training, and periodic performance evaluation, which are also necessary. Thus, by adopting the right information technology strategy, public accounting firms can improve their operational effectiveness, enhance client satisfaction, and strengthen their competitive position in the rapidly changing and competitive market. The IT Balanced Scorecard can serve as an effective framework in creating IT strategies because the distribution of strategies is evenly spread across all parts of the company, enabling the company to develop not only from a financial perspective but also from a non-financial one. The implementation of IT strategies is expected to help accounting firms achieve the goals, vision, and mission of the company and assist companies in implementing or planning IT strategies.